Field demonstration of an optical fiber hydrophone for seismic monitoring at Campi-Flegrei caldera. (February 2023) - Janneh, M.; Bruno, F.A.; Guardato, S.; Donnarumma, G.P.; Iannaccone, G.; Gruca, G.; Werzinger, S.; Gunda, A.; Rijnveld, N.; Cutolo, A.; Pisco, M.; Cusano, A.
Highlights: A seismic fiber optic hydrophone was designed and developed. The hydrophones were installed on seabed for earthquakes monitoring in a volcanic area. FOHs accurately sensed and recorded a seismic swarm. Abstract: In this paper, we report on the development and field test of a fiber optic seismic hydrophone. The seismic hydrophone was designed to offer performance suitable to operate with resolution down to the sea state zero in underwater environments. The sensing configuration exploits a fiber coil interferometer in Michelson configuration, wrapped around a sensitive composite cylinder. The materials and the size of the hydrophone were selected by numerical analysis in order to guarantee the desired responsivity. The sensing system was integrated in the seismologic monitoring system of the Campi-Flegrei caldera for demonstrating the operative capability of the developed system. To this aim, the hydrophone was installed in a submarine module onto the seabed in the Gulf of Pozzuoli and the optoelectronic read-out system was placed on an instrumented geodetic buoy. During the field trials, we detected several earthquakes occurred in the area and compared the results with a reference piezoelectric hydrophone. The seismic sequence was used to retrieve the sensor responsivity in the frequency range 1–80 Hz. The sensing system reaches a responsivity of about −300 nm/Pa and exhibits an average noise floor level down to 100µPa/√Hz. The comparison of the traces recorded by the optical and reference hydrophones reveals a high level of similarities with autocorrelation higher than 85 %. The reported field trial at the Campi-Flegrei caldera demonstrates the capability of optical fiber hydrophones to operate in relevant environments for seismological monitoring.